An overview of entrepreneurial competencies for business success among women micro-entrepreneurs in Malaysia / Mohd Mahfudz Idris and Saridan Abu Bakar - Idris, Mohd Mahfudz; Abu Bakar, Saridan (UiTM Cawangan Johor, 2019)
Women comprise half of the Malaysian population or 15.3 million from a total of 31.7 million people. Approximately 88 percent of women entrepreneurs in the country are involved in micro-entrepreneurs. Women micro-entrepreneurs contribute significantly through income generation and job creation. Despite the significant proportion and pivotal roles of women micro-entrepreneurs for economic development, their business success is still debatable. The number of successful women micro-entrepreneurs is still low, and they are underperforming despite the increase in their population. Thus, this paper seeks to develop a broadly-based entrepreneurial competencies model that is exclusively and mutually for women micro-entrepreneurs to succeed in their business by investigating each domain of entrepreneurial competencies. This was done based on the findings by reviewing a thorough review of literature from the local and global context about this issue. Previous studies revealed that women micro-entrepreneurs need to have necessary entrepreneurial competencies to act as a catalyst for their business success. The women microentrepreneurs need to have eight domains of entrepreneurial competencies which comprise of (a) strategic (b) commitment (c) conceptual (d) opportunity (e) organizing and leading (f) relationships (g) personal, and (h) technical competencies that are exclusively and mutually for women microentrepreneurs’ business success. Finally, the conclusion from the literature help to assess the critical issues of the low number of successful women micro-entrepreneurship, and they are underperforming in Malaysia. Furthermore, understanding on every domain of entrepreneurial competencies for women micro-entrepreneurs would also ascertain which of these competencies are to be included in the entrepreneurial competencies model for women microentrepreneurs.